2020
DOI: 10.3390/ijerph17041260
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Copper Oxide Nanoparticles on the Growth of Rice (Oryza Sativa L.) Seedlings and the Relevant Physiological Responses

Abstract: Rice (Oryza sativa L.), a major staple food for billions of people, was assessed for its phytotoxicity of copper oxide nanoparticle (CuO NPs, size < 50 nm). Under hydroponic condition, seven days of exposure to 62.5, 125, and 250 mg/L CuO NPs significantly suppressed the growth rate of rice seedlings compared to both the control and the treatment of supernatant from 250 mg/L CuO NP suspensions. In addition, physiological indexes associated with antioxidants, including membrane damage and antioxidant enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(36 citation statements)
references
References 52 publications
5
30
1
Order By: Relevance
“…The toxicity of high concentrations could be attributed to the liberation of Cu ions from CuO-NPs in aqueous solutions, which is a toxicity factor in plants [ 80 ]. Several studies have reported an increase in plant growth criteria in response to the application of CuO-NPs at small concentrations [ 81 , 82 , 83 , 84 ]. Additionally, Yasmeen et al [ 85 ] have reported that the growth of wheat ( Triticum aestivum ) plants were increased when plants were soaked with Cu-NPs.…”
Section: Resultsmentioning
confidence: 99%
“…The toxicity of high concentrations could be attributed to the liberation of Cu ions from CuO-NPs in aqueous solutions, which is a toxicity factor in plants [ 80 ]. Several studies have reported an increase in plant growth criteria in response to the application of CuO-NPs at small concentrations [ 81 , 82 , 83 , 84 ]. Additionally, Yasmeen et al [ 85 ] have reported that the growth of wheat ( Triticum aestivum ) plants were increased when plants were soaked with Cu-NPs.…”
Section: Resultsmentioning
confidence: 99%
“…Toxicological concerns exist also for copper and copper oxide nanoparticles as studies indicate a strong relation between decreasing nanoparticles size and increasing phytotoxicity [ 271 , 272 , 273 ]. Some recent studies also indicate effects on plastids, mitochondria, protoplasm, and membranes for Hordeum sativum distichum [ 274 ] or Abelmoschus esculentus [ 275 ].…”
Section: Toxicity Studiesmentioning
confidence: 99%
“…na: data not available. Data and plant species from: [109] Solanum lycopersicum ; [110] Oryza sativa ; [111] Triticum aestivum ; [112] Arachis hypogaea ; [113] Calendula officinalis ; [114] Nicotiana tabacum ; [115] Triticum aestivum ; [116] Vigna unguiculata ; [117] Triticum aestivum ; [118] Solanum lycopersicum ; [119] Oryza sativa ; [120] Raphanus sativus ; [121] Vigna radiata ; [122] Oryza sativa ; [123] Phaseolus vulgaris ; [124] Oryza sativa ; [125] Fragaria × ananassa ; [126] Raphanus sativus . …”
Section: Phenotypic Responses Induced By Nms In Microorganisms and Plantsmentioning
confidence: 99%